The impact of women’s participation, leadership, and units on rebel organizations’ goal attainment and conflict outcomes - Brewer, Catherine (My University, 2026)
Conflicts end not only through easily identifiable outcomes, but also through the goals that rebel organizations pursue and achieve. Intermediate goals are a necessary step toward outcomes, but are rarely discussed, except in terms of interim governments and power-sharing agreements. End goals help to guide a rebel organization’s mission and vision for the future. These two types of goals then help the rebel organization meet a successful outcome, specifically a peace agreement or a rebel victory. Women may play critical roles in helping rebel groups achieve their goals. Women’s inclusion in roles as participants, leaders, and in all-women units and in frontline and non-combat positions provides the rebel organization with a wealth of potential for success. Using Firth’s logistic regression, I analyzed the impact of these women’s roles and positions on goal attainment and outcomes. I found that women leaders and units with no specific role were essential to meeting intermediate goals, but I found very little support for women being impactful in any role or position for complete goal attainment, except potentially for non-combat women’s units. When analyzing specific outcomes, frontline and non-combat participants, frontline leaders, and women’s units, specifically frontline units, were significantly impactful for a rebel organization to successfully negotiate a peace agreement. Women participants and frontline leaders were associated with rebel victory as well.
Keywords: Women; Rebel Organizations; Goal Attainment; Outcomes